Resource management optimisation of OFDM-IDMA system for 5G multi-tier backhaul networks - Altaf Osman Mulani; Nilima S. Warade; Osamah Ibrahim Khalaf; Qusay Bsoul; Dattatray Waghole; Makarand Jadhav; Vaishali Satish Jadhav; Akram Bennour; Firas Zawaideh; Deema Mohammed Alsekait; Diaa Salama AbdElminaam (Egyptian Informatics Journal)
In anticipation of 5G, there has been a surge in demand lately for the quickest wireless networks. Radio interference and resource control are the primary problems in heterogeneous and multi-tier 5G networks. The capacity of a 5G network has been enhanced by the suggested resource and interference control technique. The QPSK modulation technique is used in the simulation on a MIMO channel. In addition to achieving the maximum system throughput, the suggested power control and joint distributed cell association approach lowered energy usage, delayed traffic, and latency.Furthermore, a reduced signal-to-interference ratio is necessary for high-priority consumers. Comparing the simulation results to the current resource-aware and distance-aware approaches, it is evident that an improvement in total data rate performance is achieved. As a result, the suggested strategy may effectively manage radio resources for 5G networks. Ultimately, there is a 35 % increase in QoS performance in terms of throughput, a 32 % reduction in delay, and a 28 % reduction in jitter.